2018
DOI: 10.1108/jd-04-2017-0065
|View full text |Cite
|
Sign up to set email alerts
|

Developing a model to explore the information seeking behaviour of farmers

Abstract: Purpose Generating an in-depth understanding of information needs and seeking behaviour is important both for restructuring existing agricultural information systems (ISs) and for creating new ISs. Many information seeking models have been developed over the years, most are narrowly focused on a specific role or discipline. However, no such specific model has been developed in reference to agriculture or an allied discipline. Thus, the purpose of this paper is to develop a model to explore the information seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
(87 reference statements)
1
13
1
1
Order By: Relevance
“…The occasional information needs of citrus farmers were centered on labor availability, agrochemicals, how to stop fruit drop, weather, irrigation plans and management, pesticides application, health and safety information, buyers, collections and traders, and herbicides. These results were quite logical and consistent with the findings of previous researches such as Kabir, Roy, and Kuri (2014), Kumar (2014), Mahindarathne and Min (2018), Naveed andAnwar (2013, 2015), and Radad, Behzadi and Zadehrahim, (2017) who also reported that the rural farmers need this type of information from time to time. Furthermore, the citrus farmers needed information least frequently on transportations, climatic change adaption and mitigation, intercropping, eco-friendly farming practices, modern techniques, equipment and tools, water testing and management, and training, field trips, workshops, etc.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The occasional information needs of citrus farmers were centered on labor availability, agrochemicals, how to stop fruit drop, weather, irrigation plans and management, pesticides application, health and safety information, buyers, collections and traders, and herbicides. These results were quite logical and consistent with the findings of previous researches such as Kabir, Roy, and Kuri (2014), Kumar (2014), Mahindarathne and Min (2018), Naveed andAnwar (2013, 2015), and Radad, Behzadi and Zadehrahim, (2017) who also reported that the rural farmers need this type of information from time to time. Furthermore, the citrus farmers needed information least frequently on transportations, climatic change adaption and mitigation, intercropping, eco-friendly farming practices, modern techniques, equipment and tools, water testing and management, and training, field trips, workshops, etc.…”
Section: Discussionsupporting
confidence: 91%
“…The agro-technological information needs of the Zambian small-scale farmers were centered on farmland maintenance, irrigation, feeds and feeding, feed additives, forestry machinery, farm building, and land drainage (Kalusopa, 2005). An investigation by Mahindarathne and Min (2018) developed a model to explore farmers' information seeking behaviour based on Wilson's model. The adapted model not only provides theoretical and empirical bases for investigating information seeking behaviour of farmers but can also be useful for promotion of information studies in agriculture.…”
Section: Information Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is as a result of rapid changes in how information is generated and used. Such frameworks help with, developing new systems for information dissemination, addressing the need for understanding the target community before propagation of information (Msoffe and Ngulube, 2016), predicting the information-seeking behaviour of farmers (Mahindarathne and Min, 2018), placing emphasis on socio-economic factors in the technology adoption decisions (Lubua and Kyobe, 2019), or establishing factors that influence increased adoption of farm input and their relationships (Kante et al, 2019).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%